Collaborative Writing with Padlet: : A Strategy for Improving Writing Skill in Senior High School - Tarisa Andela Putri; Yuyun Hendrety; Gaya Tridinanti (Didascein : Journal of English Education, 2026)
Collaborative writing is a method where students work in pairs or small groups to generate ideas, provide feedback to one another, and construct written texts together. The purposes of this research were (1) to find out whether or not it was effective to improve students’ writing skill achievement through collaborative writing using Padlet, and (2) to find out whether or not there was any significant difference in students’ writing skill achievement between students who were taught through collaborative writing using Padlet and those who were not. A quasi-experimental design was applied in this research. The population involved all tenth-grade students of SMA Negeri 11 Palembang during the 2024/2025 academic year. A total of 70 students were selected as the sample of this study using a purposive sampling technique and assigned to experimental and control groups. Writing tests were administered to collect the data. The obtained data were analyzed using a paired sample t-test and an independent sample t-test. The results of the paired sample t-test showed that collaborative writing using Padlet was effective in improving students' writing skills. The independent sample t-test showed that there was a significant difference in writing skills between students who were taught collaborative writing using Padlet and those who were not. The results indicated that it was effective to improve students’ writing skill achievement through collaborative writing using Padlet. There was also a significant difference in students’ writing skills between students who were taught through collaborative writing using Padlet and those who were not.